Exploration of Anticancer Activity Potential and Molecular Docking Study of Essential Oil Blumea balsamifera Leaves Against Several Breast Cancer Cell Lines (T47D and MCF-7) - Rahmi Vika Ulia; Toto Raharto (Molekul, 2026)
ABSTRACT. The sembung plant (Blumea balsamifera) is a wild shrub traditionally used to treat various diseases, including cancer. However, comprehensive studies regarding the chemical composition, molecular docking interactions, and anticancer activity of its leaves essential oil against breast cancer cells are still limited. Therefore, this study aimed to explore the anticancer potential and molecular docking interactions of B. balsamifera leaves essential oil against estrogen receptor-positive breast cancer cell lines (T47D and MCF-7). The essential oil was isolated using hydrodistillation and analyzed using Gas Chromatography–Mass Spectrometry (GC-MS), which identified 36 chemical compounds. The major compounds were camphor (32.56%), caryophyllene (17.04%), 7-epi-silphiperfol-5-ene (5.33%), and gamma-eudesmol (5.01%). Preliminary cytotoxicity screening using the Brine Shrimp Lethality Test (BSLT) demonstrated strong cytotoxic activity with an LC50 value of 17.17 µg/mL. Molecular docking analysis against estrogen receptor alpha (ER-α) showed favorable binding affinity values ranging from -6.444 to -8.434 kcal/mol. Furthermore, the essential oil exhibited moderate anticancer activity against T47D and MCF-7 breast cancer cells, with IC50 values of 39.52 µg/mL and 30.18 µg/mL, respectively. These findings suggest that B. balsamifera leaves essential oil has potential as a natural source of anticancer compounds for further investigation. Keywords: Anticancer, Blumea balsamifera, molecular docking, MTT assay